Frequency of use minute concentrations of cadmium in aqueous solution by near infrared spectroscopy and aquaphotomics - Hesti Meilina; A. Putra; R. Tsenkova (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Cadmium (Cd) is a common industrial pollutant with long biological half-life, which makes it a cumulative toxicant. Near-infrared spectroscopy has been successfully used for quick and accurate assessment of Cd content in agricultural materials, but the development of a quick detection method for ground and drinking water samples is of equal importance for pollution monitoring. Metals have no absorbance in the NIR spectral range, thus the methods developed so far have focused on detection of metal-organic complexes. This study uses Aquaphotomics to measure Cd in aqueous solutions by analyzing the changes in water spectra that occur due to water-metal interaction. Measurements were performed with Cd (II) in 0.1 M HNO3, in the 680-1090 nm (water second and third overtones) and 1110-1800 nm (water first overtone) spectral regions, and were subjected to partial least-square regression analysis. A concentration of Cd from 1 mg L-1 to 10 mg L-1 could be predicted by this model with average prediction correlation coefficient of 0.897. The model was tested by perturbations with temperature and other metal presence in the solution. The regression coefficient showed consistent peaks at 728, 752, 770, 780, 1362, 1430,1444, 1472/1474 and 1484 nm under various perturbations, indicating that these water absorbance changes were due to Cd presence. The residual predictive deviation values (RPD) were greater than 2, indicating that the model is appropriate for practical use